The Effect of Learning Independence on Learning Outcomes in Fiqih Subjects of Class X MAN 3 Inhil - Aprizal, Aprizal; Dewi, Puti Andam (Peneliti.net, 2025)
The problem in this study is that the results of students in the subject of fiqh in class X are still low below the maximum completeness criteria. The purpose of this study was to determine the effect of independence on the learning outcomes of students in class X MAN. This type of research is quantitative with ex post facto. The population consists of 54 students of X MAN 3 Inhil. Data collection used questionnaire data on learning independence and documentation of mid-semester exam learning outcomes. Data analysis used normality tests and linearity tests. The data analysis technique was quantitative. The results of the data analysis concluded that there was an effect of learning independence on the learning outcomes of students in the subject of fiqh MAN 3 Inhil